2021
DOI: 10.3390/genes12060790
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Estrogen Receptor 1 Gene in the Paraspinal Muscles of Girls with Idiopathic Scoliosis and Its Association with Disease Severity

Abstract: Idiopathic scoliosis (IS) is a multifactorial disease with epigenetic modifications. Tissue dependent and differentially methylated regions (T-DMRs) may regulate tissue-specific expression of the estrogen receptor 1 gene (ESR1). This study aimed to analyze methylation levels within T-DMR1 and T-DMR2 and its concatenation with ESR1 expression of IS patients. The study involved 87 tissue samples (deep paravertebral muscles, both on the convex and the concave side of the curve, and from back superficial muscles) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…According to the research performed, a total of 40 papers [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] met the inclusion criteria and were considered for review. Of these studies, twenty-one [ 18 , 19 , 21 , 24 , 31 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the research performed, a total of 40 papers [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] met the inclusion criteria and were considered for review. Of these studies, twenty-one [ 18 , 19 , 21 , 24 , 31 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 ,…”
Section: Resultsmentioning
confidence: 99%
“…According to the Oxford level of evidence scale, ten [ 16 , 17 , 27 , 28 , 29 , 32 , 46 , 48 , 49 , 53 ] of the included studies had a level of evidence IV, twenty-six [ 18 , 19 , 20 , 21 , 23 , 24 , 26 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 , 47 , 50 , 51 , 52 , 54 , 55 ] studies had a level of evidence III, while the remaining studies had a level of evidence II [ 22 , 25 , 30 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted studies have reported associations between methylation and IS near the COMP [73] and PITX1 [74] genes. Two recent studies [75,76] of ESR1 and ESR2 methylation from paravertebral muscle tissue in females with IS supports potential interrelationship between sex hormone levels, methylation, and the clinical manifestation of IS. ESR1 methylation levels from paravertebral muscle tissue on the concave side of curve were associated with curve severity [75], and furthermore, ESR2 promoter methylation levels differed between concave and convex sides of the curves [76].…”
Section: Introductionmentioning
confidence: 84%
“…Two recent studies [75,76] of ESR1 and ESR2 methylation from paravertebral muscle tissue in females with IS supports potential interrelationship between sex hormone levels, methylation, and the clinical manifestation of IS. ESR1 methylation levels from paravertebral muscle tissue on the concave side of curve were associated with curve severity [75], and furthermore, ESR2 promoter methylation levels differed between concave and convex sides of the curves [76]. Epigenome-wide discovery analyses in MZ twins are limited to studies including only one [77] and two [78] MZ twin pairs discordant for IS.…”
Section: Introductionmentioning
confidence: 84%